2020
DOI: 10.15672/hujms.474649
|View full text |Cite
|
Sign up to set email alerts
|

Solvability of a system of higher order nonlinear difference equations

Abstract: In this paper we show that the system of difference equations x n = ay n−k + dy n−k x n−(k+l) bx n−(k+l) + cy n−l , y n = αx n−k + δx n−k y n−(k+l) βy n−(k+l) + γx n−l , where n ∈ N 0 , k and l are positive integers, the parameters a, b, c, d, α, β, γ, δ are real numbers and the initial values x −j , y −j , j = 1, k + l, are real numbers, can be solved in the closed form. We also determine the asymptotic behavior of solutions for the case l = 1 and describe the forbidden set of the initial values using the obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Clearly, the trajectory above shows that fluctuations in foreign exchange are within a band and hence the policy, if it can be sustainably maintained, could prevent the market from sliding into an uncontrollably erratic path that could be induced by stochastic and chaotic tendencies. (For different modelling exercises that could be used for the purpose of developing alternative stochastic policies, see Kara (2007Kara ( , 2013. )…”
Section: Topological Conjugacy and Chaosmentioning
confidence: 99%
“…Clearly, the trajectory above shows that fluctuations in foreign exchange are within a band and hence the policy, if it can be sustainably maintained, could prevent the market from sliding into an uncontrollably erratic path that could be induced by stochastic and chaotic tendencies. (For different modelling exercises that could be used for the purpose of developing alternative stochastic policies, see Kara (2007Kara ( , 2013. )…”
Section: Topological Conjugacy and Chaosmentioning
confidence: 99%
“…Recently, in [27] we showed that the following difference equations system     ) can obtain by taking 2 k  in system (1.5). Finally, we showed that the following higher-order system of nonlinear difference equations…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that if we want to understand our models, we need to know the behavior of the solutions of the equations of the models, and this fact will be possible if we can solve in closed form these equations. One can find in the literature a lot of works on difference equations where explicit formulas of the solutions are given, see for instance [1], [2], [5], [8], [9], [10], [7], [12], [11], [13], [16], [15], [14], [17], [18], [21], [20], [22]. Such type of difference equations and systems is called solvable difference equations.…”
Section: Introductionmentioning
confidence: 99%